MODIFICATION OF STUDENT ASSESSMENT CRITERIA AS A CONDITION OF MOTIVATION INCREASING FOR PHYSICAL EDUCATION LESSONS - E. M. Revenko (Образование и наука)
The aim of the study is the rationale for the changes assessment criteria student performance in physical education on the basis of individualtypological variants of age development.The main task of PE lessons is formation of steady need for systematic occupations by physical exercises. However, there is an obvious tendency of interest decrease of school students to occupations by physical culture and their extremely low physical activity that is reflected on health of younger generation. The common unified requirements for control standards don't promote development of motivation to occupations by physical culture of considerable part of school students. The obligatory accounting of specific features of age development is necessary for optimization of the organization of physical training.Methods. Motor abilities of school students are studied based on the measurements of the strength, strength endurance, speed and power abilities, speed, and aerobic endurance. The general physical development of each student is calculated by transferring the absolute values of the test points in the program «Presidential race». Dynamics of general physical development is calculated by comparing the indicators of physical development at the beginning and the end of the school year.The study of mental abilities of 8, 10, and 11th grade pupils is carried out by R. Amthauer tests adopted by L. A. Yasukova, and the study of mental abilities of 6th grade students is carried out by intellectual test (GIT). Typological peculiarities of manifestation of the nervous system properties – the power of the nervous system, mobility of excitation and inhibition, the balance on the «external» and «internal» balance sheets are investigated with the use of arbitrary motor methodologies proposed by E. P. Ilyin.Results. It is experimentally established that during adolescence there is a mismatch in time of the dynamics peaks of motor abilities and intelligence. So, the sixth graders dynamics of motor abilities development is significantly higher for students with low dynamics of intelligence, from which it follows that at the age of 12–13 years high pace of development of motor abilities coincides with relatively less dynamic intelligence, and vice versa.As they mature in 8–11th grade the overall view changes - high dynamics of motor abilities development coincides with the high dynamics of intelligence. However, it is found out that students in 6th grade with a strong nervous system and the predominance of excitation of internal balance have a higher dynamics of development of motor abilities with the background of low dynamics of intelligence. On the contrary, sixth grade pupils with relatively weak nervous system and the predominance of inhibition on the internal balance characteristic have shown better dynamics of intelligence and low dynamics of motor abilities development.Consequently, there is reason to believe that during adolescence, biological factors influence much on the ratio of the dynamics of mental and motor areas of the personality. As a result, some teens dominate the development of the mental sphere, while the others dominate in the motor one. In this regard, common unified control standards and requirements do not correspond to the development of motivation for physical education lessons for a specific part of the students.Scientific novelty. The scientific experimental data on the ratio of the dynamics of development of motor abilities and intellect in the process of growing boys, different typological features of the nervous system properties are presented for the first time. The obtained experimental data can serve as a basis for the development of differentiated criteria for evaluating student performance in physical education classes.Practical significance. The results of the study can serve as a basis for the development of new approaches to students’ assessment during physical education lessons. Materials of research can be useful to PE teachers and training specialists. Reorientation of assessment system of pupils’ achievements at PE lessons on specific features of age development will allow leveling down negative attitude of children to physical exercises.